KORELASI SKOR MONTREAL COGNITIVE ASSESSMENT VERSI INDONESIA (MoCA-Ina) DENGAN TINGKAT KERENTAAN PASIEN LANSIA - Fredia Heppy; Tati Khairina; Annisa Syazatul Isny (Nusantara Hasana Journal, 2025)
Cognitive impairment has frequently been found as a geriatric syndrome in the elderly. It is vary from mild cognitive impairment to severe dementia. In cases of dementia, cognitive impairment has been found concomitanly with decreasing of daily activities characterized by dependence on the environment. Caring for dementia patients will increase many sector health burdens, indeed preventive actions are needed by managing risk factors such as frailty levels and finding new cases of cognitive impairment earlier with sensitive screening instruments. The Montreal Cognitive Assessment (MoCA) is a superior instrument for detecting mild cognitive impairment. The study aims to examine the correlation of MoCA-Ina scores with the frailty status of elderly patients. This study is an observational analytic study with a cross-sectional study design. The research subjects were taken using consecutive techniques. Based on the analytical formula for correlative numerical data, a sample of 95 subjects was obtained. The results of this study using Spearmen's rho correlation analysis has been obtained a significant relationship between MoCA-Ina scores and frailty levels with p = 0.000 and moderate correlation with correlation coefficient of r = -0.455. The study concluded that there was a moderate correlation between MoCA-Ina scores and the frailty levels of elderly subjects.